Research on the Quality Indicators of Semi-Finished Vegetable Sauce-Pastes - Muxammadjonovich, Xojiyev Rustam; Rustamovna, Abduraxmanova Muazzam (American Journal of Biodiversity, 2025)
The article examines the results of studying the quality indicators of semi-finished vegetable sauce-pastes. Organoleptic characteristics were investigated, physicochemical properties were analyzed, and the energy value of semi-finished vegetable sauce-pastes was calculated.